2001
DOI: 10.1046/j.1365-2559.2001.01138.x
|View full text |Cite
|
Sign up to set email alerts
|

Two relatively distinct patterns of ameloblastoma: an anti‐apoptotic proliferating site in the outer layer (periphery) and a pro‐apoptotic differentiating site in the inner layer (centre)

Abstract: Ameloblastoma has much more apoptosis-inhibiting protein than the apoptosis-modulating protein. Ameloblastoma has two relatively distinct patterns, an anti-apoptotic proliferating site in the outer layer (periphery) and a pro-apoptotic differentiating site in the inner layer (centre). The acanthomatous area, which was stained strongly by bak antibody and contained numerous terminally apoptotic cells, was considered as the differentiated area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
59
1
11

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 18 publications
11
59
1
11
Order By: Relevance
“…Since KOT had been classified as an odontogenic cyst, several authors have compared cell proliferation between KOT and odontogenic cysts (8,12,13). Although several authors have assessed cell proliferation and apoptosis in the odontogenic epithelium in AM and in the epithelial lining in KOT (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), few studies have compared cell proliferation between these tumors (7,8,11) and no previous study has simultaneously evaluated cell proliferation and apoptotic indexes in AM and KOT, comparing both lesions. Therefore, this is the first study assessing comparatively cell proliferation and apoptosis indexes in AM and KOT, although tissue cell population is controlled by a balance among these processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since KOT had been classified as an odontogenic cyst, several authors have compared cell proliferation between KOT and odontogenic cysts (8,12,13). Although several authors have assessed cell proliferation and apoptosis in the odontogenic epithelium in AM and in the epithelial lining in KOT (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), few studies have compared cell proliferation between these tumors (7,8,11) and no previous study has simultaneously evaluated cell proliferation and apoptotic indexes in AM and KOT, comparing both lesions. Therefore, this is the first study assessing comparatively cell proliferation and apoptosis indexes in AM and KOT, although tissue cell population is controlled by a balance among these processes.…”
Section: Discussionmentioning
confidence: 99%
“…This antigen is considered to be a better specific marker of proliferating cells (23). Although several authors have used Ki-67 to access cell proliferation in KOT (12,13) and AM (19,20), few studies have compared cell proliferation between AM and KOT using the Ki-67 (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results suggested that these epithelial cyst linings were neither simple nor neoplastic, but comparatively differentiated stratified squamous epithelia. The bcl-2 proto-oncogene is a member of a gene family in the suppressors of the programmed cell death (17,(27)(28)(29). Recent studies have suggested that there is a close relationship between bcl-2 protein expression and cell population which are long lived, and/or with high proliferation ability (3,29).…”
Section: Discussionmentioning
confidence: 99%
“…The bcl-2 proto-oncogene is a member of a gene family in the suppressors of the programmed cell death (17,(27)(28)(29). Recent studies have suggested that there is a close relationship between bcl-2 protein expression and cell population which are long lived, and/or with high proliferation ability (3,29). Immunoreactivity for bcl-2 protein has been detected in the enamel organs and the dental lamina of tooth germs as well as in most neoplastic cells of ameloblastoma (3,30).…”
Section: Discussionmentioning
confidence: 99%